Pengembangan Potensi Desa Somongari Sebagai Desa Agrowisata Di Kabupaten Purworejo - Bambang Irjanto; Heri Winarto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Somongari Village is a village in Purworejo Regency and currently Somongari Village is entering the tourist village development stage. However, there are obstacles that make the tourism village development program in Somongari Village less than optimal. These obstacles include not having properly implemented the tourism village roadmap listed in the Village RPJMD, the need to develop a network of partnerships with other parties to develop tourism villages, the need to strengthen village organizations (such as KWT, BUMDes and Karang Taruna). For this reason, a Community Service Program is being carried out with output targets: 1). There is a potential roadmap for agrotourism villages in the Somongari tourist village. 2). There is an increase in organizational capacity in the village in the context of managing and developing tourist villages in Somongari Village. Stages in activities: 1). Activity planning. The service team invited Pokdarwis administrators and the local village government. 2). Activity process. This stage is aimed at finding out the level of understanding of the mentoring participants along with feedback in the form of questions from the training participants who have received knowledge transfer regarding the potential of the village and what will be developed as a tourist village. 3). End of activity. Evaluation is carried out to measure the success of all mentoring programs. The activity success indicator was determined to be 80% of participants able to implement material to strengthen and improve the tourist village in Somongari Village.